Research on 4G Mobile Terminal Data Throughput Test - Liang Kang; Lianbo Song; Long Sun; Hao Duo (Dianxin kexue)
Data throughput test of 4G mobile terminal was used to validate whether the data throughput can meet the standard requirements，which has important influence on ensuring the high speed access. Three algorithms of the data throughput test：instrument test，indoor network test，and field test，were introduced. Comparing the test environment，efficiency，problem reproduction and user experience，an introduction of the current status of data throughput test algorithm was given. Furthermore，a trends of the development in the future was presented.